FBI : Hemlock Bay - Book 6 - Coulter, Catherine (New York : G.P. Putnams Sons, 2001)
While embroiled in a case involving two kidnapped teenage boys, FBI agent Dillon Savich must investigate the latest suicide attempt of his youngest sister, tied to four paintings she inherited from her grandmother.
Keywords: United States. -- Federal Bureau of Investigation -- Fiction; Government investigators -- Fiction; Savich, Dillon (Fictitious character) -- Fiction; Sherlock, Lacey (Fictitious character) -- Fiction; Married people -- Fiction; Washington (D.C.) -- Fiction; Maryland -- Fiction; Detective and mystery fiction; Thrillers (Fiction)